Towards the Sustainable Removal of Heavy Metals from Wastewater Using Arthrospira platensis: A Laboratory-Scale Approach in the Context of a Green Circular Economy - Lamprini Malletzidou; Eleni Kyratzopoulou; Nikoletta Kyzaki; Evangelos Nerantzis; Nikolaos A. Kazakis (Applied Sciences)
The use of living Arthrospira platensis (A. platensis) cultures emerges as a promising green solution for the bioremediation of water contaminated by toxic metal waste. The scope of the present study is to evaluate the microalga’s potential in heavy metal remediation, in the case of multi-metal-treated (multi-MT) systems. For this reason, A. platensis cultures were exposed to mono- and multi-metal solutions of Cu, Cd, Ni, Pb, and Zn, and their metal adsorption ability was investigated. The heavy metal removal efficiency of A. platensis cultures was evaluated using atomic absorption spectroscopy (AAS). Additionally, the cultures were examined using Fourier transform infrared (FTIR) spectroscopy, Near-Infrared (NIR) Spectroscopy, UV-Vis spectrophotometry, and optical microscopy, together with pH and electrical conductivity (EC) measurements to evaluate the quality of the cultures and the changes induced by heavy metal stress. The results showed that metal removal is still efficient in multi-MT cultures. In particular, Cu, Cd, Pb, and Zn removal of multi-MT cultures is elevated or relative to the respective removal of the mono-metal-treated (mono-MT) cultures, showing a synergistic or cooperative interaction between the metals, while the removal of Ni of multi-MT cultures decreased compared to Ni of mono-MT cultures, showing an antagonistic interaction to the other metals. The study shows that A. platensis is considered an effective microalga toward the bioremediation of multi-metal polluted cultures.